Pertumbuhan Bunga Matahari di Pesisir Pantai dengan Pemberian Mikoriza dan Pupuk Kotoran Ayam - Muhsanati, M; Obel, O; Erona, Meisilva (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Sunflower is one of the oil-producing plants with great potential to be developed as food raw materials, industrial materials, medicinal and beauty ingredients. Sunflower development needs to be carried out on various lands in Indonesia. One of them is in the coastal area. However, these lands are marginal lands so improvements need to be made through various technological innovations. One of them is the application of mycorrhizae and chicken manure fertilizer. This study aims to determine the effect of mycorrhizae and chicken manure on sunflower growth on coastal land. This research was conducted using a randomized block design consisting of two factors, namely mycorrhizae and chicken manure, which were repeated 3 times. The results of the study showed that the application of mycorrhizal and chicken manure fertilizers increased the percentage of seedlings growing, plant height, leaf number, and stem diameter of sunflowers on coastal land.